Cinematography Aesthetic Analysis of the Controversial Documentary Film “Ice Cold: Murder, Coffee, and Jessica Wongso” - Kristina, Ni Putu Ayu Cempaka Riska Intan (Journal of Aesthetics, Creativity and Art Management, 2025)
Documentary film is a medium used to present reality through visuals recorded based on existing facts. In its presentation, this film can include human thoughts, referring to documentary film theories that depict subjects in the form of real people, events or situations. This study aims to analyze the cinematographic aesthetics of the documentary film entitled "Ice Cold: Murder, Coffee, and Jessica Wongso" which depicts a horrendous murder incident in Indonesia several years ago. Using qualitative methods based on literature studies from various sources, this study found that this film uses direct recording methods and reconstruction of events to convey information and build the audience's opinion regarding the events discussed. The research results show that "Ice Cold: Murder, Coffee, and Jessica Wongso" is included in the conventional expository category, which is often used in television documentary production. This type places more emphasis on narrative and logical argumentation, with a single narrator who is often dubbed the "voice of God".